Tari RESULT - Pratama, I Putu Oka Surya; Kasih, Ni Nyoman; Saputra, I Putu Bagus Bang Sada Graha (Jurnal IGEL : Journal Of Dance, 2024)
Result is a contemporary dance work whose idea comes from dice. The creator has an interest in the form of a number game and the clash of dice which results in an uncertain number value, and is poured into the dance work Result. In the method of creating this dance work, the creator found a gambling game method that was applied spontaneously by both dancers and musicians with dice media, the creator wanted to visualize it in a dance work to try or experiment on dice media. Do not forget that the creators also used Jacqueline Smith's dance creation method, called the construction method. The construction method consists of five stages, namely I to V, each of which has a stage in the process of creating a dance work.